1977
DOI: 10.1002/jez.1402010109
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of structure and penetrability of the vitelline envelope after passage of eggs from coelom to oviduct in Xenopus laevis

Abstract: The vitelline envelope (VE) that surrounds an egg released from the ovary into the coelom of Xenopus laevis differs markedly, in structure and penetrability, from the VE surrounding an oviposited egg. In a coelomic egg, the filaments that form the VE are arranged in distinct fascicles or bundles. The exterior surface of the VE is irregular in contour and is permeated by channels. In an oviposited egg, the filaments are evenly dispersed and lack a fasciculated arrangement; the exterior surface is smooth and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 22 publications
3
45
0
Order By: Relevance
“…Similar changes have been described for other Amphibian species (11,15,12). In fact, the action during only 30 min of "pars recta" secretions makes the vitelline coat of coelomic oocytes liable to spermatic lysines.…”
Section: Conditioned Coelomic Oocytessupporting
confidence: 75%
“…Similar changes have been described for other Amphibian species (11,15,12). In fact, the action during only 30 min of "pars recta" secretions makes the vitelline coat of coelomic oocytes liable to spermatic lysines.…”
Section: Conditioned Coelomic Oocytessupporting
confidence: 75%
“…Although alterations in ZP thickness have been reported after ovulation [20], our results show that, if true, they do not affect the fasciculated configuration. However, changes in bundle association (compaction) were observed in the vitelline envelope of Xenopus, after ovulation [34], and modifications may also occur particularly in the outer layer. Differences in pig ZP between oocytes matured in vitro or in vivo may be attributed to an incomplete maturation in the first case and/ or to extracellular matrix addition in the second case [20,35].…”
Section: Texturementioning
confidence: 99%
“…Katagiri et a1 [22] have demonstrated that an extract of the pars recta region of the oviduct from Bufo Bufojuponicus can cause the morphological alteration of the CE to VE in Bufo eggs. In the eggs of Xenopus laevis, a morphological change of the CE to VE can be induced at pH 6 or 9 [2]. However, these nonphysiological conditions would not likely cause the 43K to 41K conversion demonstrated here, but could possibly Identification of the chemical nature of the processing event involved in the 43K to 41K conversion and isolation of the oviductal hydrolase catalyzing this processing event will be necessary in order to understand the ultrastructural and functional (sperm penetrability) differences in the CE and VE.…”
Section: Discussionmentioning
confidence: 99%